MAJOR ACHIEVEMENTS AND CHALLENGES OF SORGHUM (SORGHUM BICOLOR [L.] MOENCH) BREEDING AND PRODUCTION IN SOUTHWESTERN PART OF ETHIOPIA-REVIEW ARTICLE - BELETE, TEGEGN (Innovare Journal of Agricultural Sciences, 2022)
Sorghum (Sorghum bicolor [L.] Moench, Poaceaea family) (2n = 20) is the 5th most important cereal crop and is the dietary staple of more than 500 million people in 30 countries. In Ethiopia, sorghum is the third largest cereal crop in area coverage and total production preceded by tef and maize. In Ethiopia, South and Southwestern part of Ethiopia were one of major coffee growing regions and have climatic and edaphic factors that combine well to meet the requirements of both coffee and cereals. In collaboration with sorghum improvement program, Jimma research center was conducting different sorghum experiments at Omonada, Kersa, Yem special wereda, and Shebe sombo to identify adaptable technologies for agro-ecologies of southwestern part of Ethiopia. Jimma research center conducted adaptable and high yielding technologies for mid altitude and lowland areas of southwestern part of Ethiopia. Major challenging factors for sorghum improvements were lack of varieties with specific trait and adaptatibility, diseases and insects’ threat, drought and limited availability of quality seed and instability of researchers, dieases, weeds, and birds were major breeding and production threat of Southwestern Ethiopia.